2022
DOI: 10.1249/mss.0000000000002886
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Correlates of Objectively Measured Sedentary Behavior in Young Children: SUNRISE Study Results from 19 Countries

Abstract: PurposeThere is a paucity of global data on sedentary behavior during early childhood. The purpose of this study was to examine how device-measured sedentary behavior in young children differed across geographically, economically, and sociodemographically diverse populations, in an international sample.MethodsThis multinational, cross-sectional study included data from 1071 children 3–5 yr old from 19 countries, collected between 2018 and 2020 (pre-COVID). Sedentary behavior was measured for three consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additionally, the promotion of health and well‐being is a mandated component of ECE curricula (e.g., AGDE, 2022; New Zealand Ministry of Education, 2017), and ECE services generally have resources to promote physical activity and reduce sedentary time through the provision of meaningful and authentic learning experiences spread throughout the day. Despite this, international research suggests that children spend 56% of time being sedentary (Kariippanon et al, 2022) and less than 20% of their time in physical activity whilst in ECE services (Ellis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the promotion of health and well‐being is a mandated component of ECE curricula (e.g., AGDE, 2022; New Zealand Ministry of Education, 2017), and ECE services generally have resources to promote physical activity and reduce sedentary time through the provision of meaningful and authentic learning experiences spread throughout the day. Despite this, international research suggests that children spend 56% of time being sedentary (Kariippanon et al, 2022) and less than 20% of their time in physical activity whilst in ECE services (Ellis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that promoting MVPA may yield enduring advantages for body composition and physical fitness. Compared to PA, SB has negative effects on health (11,12), Sedentary behavior is commonly observed among young children, and prolonged sedentary time is associated with higher body fat composition. On the contrary, maintaining a healthy dietary nutrition during early childhood has a positive impact on reducing the risk of obesity and promoting the physical fitness of young children (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…2 The SUNRISE study reported quantitatively assessed sedentary behavior in youth from 19 countries and showed that, on average, youth spent 56% of their time awake, amounting to 7.4 hours per day, being sedentary, with children from high income and upper-middleincome countries spending a greater amount of their day being sedentary. 3 Prolonged sedentary behavior impacts multiple health domains. In 2010, the World Health Organization summarized the mortality and burden of disease attributable to selected major risks and estimated that 3.2 million people die per year due to physical inactivity, making sedentary behavior the fourth most important risk factor for mortality in the entire world accounting for 6% of all deaths.…”
Section: Introductionmentioning
confidence: 99%